Laccase and Manganese Peroxidase (MnP) Activities in the White-Rot Fungus Trametes hirsuta in Response to Aromatic Compounds - Isa Nuryana; Zidny Ilmiah; Ade Andriani; Yopi Yopi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2019)
The current interest in exploring white-rot fungi has been concentrated in increasing their ligninolityc enzyme production such as laccase and manganese peroxidase (MnP) due to the great value in industrial application. The presence of appropiate inducers can enhance the enzyme production. Hence, the aim of the study was to investigate the activity of laccase and MnP in response to various aromatic compounds. The fungus Trametes hirsuta was cultured in Glucose Yeast Peptone (GYP) broth (pH 5.0) with the addition of 0.5% of sorghum biomass as substrate. The cultures were then incubated on rotary shaker at 150 rpm at 27oC. The 7-day-old cultures were then supplemented with different aromatic compounds, namely caffeic acid, gallic acid, syringic acid, trans-cinnamic acid, vanillin, and veratryl alcohol. Our results demonstrated that veratryl alcohol, gallic acid and vanillin gave an inductive effect on the value of laccase and MnP activities, with vanillin showing the highest induction. On the contrary, the level of laccase and MnP activities remained low in the presence of aromatic compound such as syringic acid, trans-cinnamic acid and caffeic acid. To conclude, our study reveals that aromatic compounds can be potential as inducers and may contribute to the improvement of laccase and MnP productivity by T. hirsuta.